Conciencia tributaria en trabajadores de Electro Oriente S.A. Iquitos primer trimestre año 2024 - Ramirez Garcia, Estefany Judith (2025)
The objective of the research was to determine the level of tax awareness of the workers of Electro Oriente S.A. in Iquitos during the first quarter of 2024. The type of study used was basic, and the design was non experimental. This also led to important findings such as the low level of trust towards the entities that manage taxes. Therefore, the work concluded that the level of tax awareness of the workers of Electro Oriente S.A. in Iquitos during the first quarter of 2024 is regular, with a total percentage of 89%.